Tethered capsule en face optical coherence tomography for imaging Barrett’s oesophagus in unsedated patients - Qin Huang; Kaicheng Liang; Osman O Ahsen; Annalee Murphy; Jason Zhang; Tan H Nguyen; Benjamin Potsaid; Marisa Figueiredo; Hiroshi Mashimo; James G Fujimoto (BMJ Open Gastroenterology)
Objective Barrett’s oesophagus (BE) screening outside the endoscopy suite can identify patients for surveillance and reduce mortality. Tethered capsule optical coherence tomography (OCT) can volumetrically image oesophageal mucosa in unsedated patients and detect features of BE. We investigated ultrahigh-speed tethered capsule swept-source OCT (SS-OCT), improved device design, developed procedural techniques and measured capsule contact, longitudinal pullback non-uniformity and patient toleration.Design OCT was performed in 16 patients prior to endoscopic surveillance/treatment. Unsedated patients swallowed the capsule with sips of water and the tether was pulled back to image the oesophagus. SS-OCT at 1 000 000 A-scans/s enabled imaging 10 cm oesophageal lengths in 10 s with 30 µm transverse and 8 µm axial resolution. Capsule contact, longitudinal image coverage and patient toleration were assessed.Results Nine patients had non-dysplastic BE, three had ablative treatment-naïve neoplasia and four had prior ablation for dysplasia. Dry swallows facilitated capsule transit through the lower oesophageal sphincter (LES), and waiting 10 s before pullback reduced swallow induced LES relaxation. Slow nasal inhalation facilitated capsule retrieval and minimised gag reflex. The procedure was well tolerated. Ultrahigh-speed SS-OCT generated cross-sectional and subsurface en face images showing BE features, while subsurface en face images were required to assess the gastro-oesophageal junction. Candidate features of dysplasia were also identified which could inform follow-up endoscopy/biopsy. BE features were seen in all patients with histologically confirmed BE. Mean capsule contact over BE was 75%±27% for all patients and better in short segment BE. Mean longitudinal image coverage over BE was 59%±34% and better for long segment BE.Conclusions Ultrahigh-speed tethered capsule SS-OCT can image en face and cross-sectional mucosal features over wide areas. Device and procedure optimisation improved performance. BE features could be identified in all patients, but limited capsule contact and longitudinal coverage could cause sampling errors for focal pathologies.